Strategi Contextual Teaching And Learning (CTL) dalam Pembentukan Minat Belajar Siswa - Nur, Siti; Arlina, Arlina; Aldi , Muhammad; Sastra , Purnama; Adawiyah, Rabiatul (Comit: Communication, Information and Technology Journal, 2024)
The purpose of this journal is to examine contextual teaching and learning strategies in forming students' interest in learning. The method used in this research is library research (Library Research). The research results that can be obtained from researchers, that from the educational level, contextual teaching and learning strategies are able to restore and shape children's learning interests, this strategy can help students to be smarter, active, and able to think critically, giving rise to new enthusiasm that shapes interest. learning for every child/student at every level of education. This will be more advanced for the cognitive, affective and psychomotor development of students in learning. Keywords: Strategy, Formation, Learning